Tanycyte Gene Expression Dynamics in the Regulation of Energy Homeostasis - Langlet, Fanny (Frontiers in Endocrinology, 2019)
Animal survival relies on a constant balance between energy supply and energy expenditure, which is controlled by several neuroendocrine functions that integrate metabolic information and adapt the response of the organism to physiological demands. Polarized ependymoglial cells lining the floor of the third ventricle and sending a single process within metabolic hypothalamic parenchyma, tanycytes are henceforth described as key components of the hypothalamic neural network controlling energy balance. Their strategic position and peculiar properties convey them diverse physiological functions ranging from blood/brain traffic controllers, metabolic modulators, and neural stem/progenitor cells. At the molecular level, these functions rely on an accurate regulation of gene expression. Indeed, tanycytes are characterized by their own molecular signature which is mostly associated to their diverse physiological functions, and the detection of variations in nutrient/hormone levels leads to an adequate modulation of genetic profile in order to ensure energy homeostasis. The aim of this review is to summarize recent knowledge on the nutritional control of tanycyte gene expression.